Desouza's forms and precedents of conveyancing - Datta, C.R. (Calcutta, 2001)
This is a practical and comprehensive book on the subject of conveyancing, legal drafting of agreements, deeds, etc. A new chapter on computer contracts is also added.
Keywords: Law